Method for resource utilization of fine wax decoloring waste activated carbon

CN122940168APending Publication Date: 2026-10-20CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611118868.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了克服现有技术存在的废活性炭再生方法制备的再生活性炭存在性能较差、生产成本较高、再生周期长以及效率低的问题,提供了一种精蜡脱色废活性炭资源化利用方法

Benefits of technology

[0018]按照本发明的技术方案,在无烟煤基活性炭常规生产工艺的基础上,利用精蜡脱色废活性炭中的木质炭和硅藻土具有的多孔结构和骨架特性,在混合过程中作为成孔剂和增强剂,一方面在炭化和活化阶段促进孔隙发育,另一方面能显著提高活性炭的机械强度和耐磨性,使其与无烟煤协同作用从而提高最终活性炭的吸附能力和机械强度,更适合动态吸附环境,同时减少无烟煤原料的使用,降低生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of coal-based carbon materials technology and discloses a method for the resource utilization of waste activated carbon decolorized by refined wax. The method includes the following steps: (1) mixing waste activated carbon and anthracite, and then ball milling the resulting mixture to obtain mixed coal powder; (2) kneading the mixed coal powder, coal tar and water, and then extruding and solidifying the resulting mixture to obtain shaped carbon strips; (3) carbonizing the shaped carbon strips under air-isolated conditions; (4) activating the carbonized material with high-temperature steam; wherein the waste activated carbon contains charcoal, diatomaceous earth and paraffin wax, and based on the total weight of the waste activated carbon, the content of charcoal is 50-60% by weight, the content of diatomaceous earth is 20-30% by weight, and the content of paraffin wax is 10-20% by weight. The resource utilization method for waste activated carbon decolorized by refined wax according to this invention can realize the efficient resource utilization of waste activated carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coal-based carbon materials technology, specifically to a method for the resource utilization of waste activated carbon from refined wax decolorization. Background Technology

[0002] Activated carbon is a porous material primarily composed of carbon elements, possessing excellent adsorption capabilities and widely used in adsorption, decolorization, and purification processes. In coal-to-oil chemical processes, the decolorization of paraffin wax often involves the synergistic adsorption of impurities (such as iron-based catalysts and pigments) from the paraffin wax. However, after use, the adsorption of a large amount of impurities clogs the pore structure of the activated carbon, causing it to lose its original adsorption properties and become solid waste that cannot be directly reused in production processes.

[0003] The main components of activated carbon from refined wax decolorization are waste wood-based activated carbon, residual paraffin wax, diatomaceous earth, and other organic matter, which have certain resource utilization value. Currently, existing solid waste treatment methods mainly include landfill, incineration, or direct regeneration. However, landfill disposal occupies land resources and poses a long-term risk of leachate pollution; incineration is energy-intensive, may produce toxic gases such as dioxins, and has large carbon emissions with no carbon resource recovery. Existing regeneration methods mainly include thermal regeneration, chemical regeneration, biological regeneration, wet oxidation regeneration, microwave regeneration, and supercritical fluid regeneration. However, thermal regeneration is energy-intensive and prone to burn-off; chemical regeneration reagents are expensive and prone to secondary pollution; biological regeneration has low efficiency and many application limitations; wet oxidation equipment is complex; microwave regeneration is difficult to heat and damages the carbon structure; and supercritical fluid regeneration has high operating costs and poor performance, making it unsuitable for refined wax decolorization solid waste and failing to achieve resource utilization, thus violating the principles of sustainable development. Therefore, developing a method for the resource utilization of refined wax decolorization solid waste has significant environmental and economic value for reducing solid waste disposal and rationally utilizing resources.

[0004] The closest existing technology uses anthracite as a raw material to produce activated carbon, preparing it through carbonization and activation processes. However, it does not address the resource utilization of waste activated carbon from wax decolorization. Furthermore, existing technologies lack mature solutions for incorporating waste activated carbon as an additive into new activated carbon production systems. Additionally, most existing technologies are limited to the single objective of "restoring adsorption performance," essentially remaining a "waste treatment" approach. They regenerate waste activated carbon to restore its adsorption performance for recycling, failing to recognize waste activated carbon as a "carbon resource." Using effective methods to prepare it into high-value-added products (such as catalyst carriers and functional materials) to achieve true "upgraded recycling" is the key to the contradiction with the principle of sustainable development. The current technical means have the following disadvantages: (1) Traditional waste activated carbon regeneration methods (such as thermal regeneration) are prone to destroying the pore structure of the activated carbon itself (such as thermal burn-off and chemical erosion), resulting in a reduction in specific surface area and a decrease in adsorption performance. In the end, the disposal of deactivated residue is still faced. Direct landfill or incineration will cause environmental pollution and waste of resources; (2) Traditional regeneration process has high energy consumption, large equipment investment, serious material loss, and additional costs are required for the disposal of waste activated carbon, increasing the overall operating cost; (3) The regeneration cycle is long, the efficiency is low, and the quality of the regenerated activated carbon is unstable, making it difficult to meet the needs of high-performance applications. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of poor performance, high production cost, long regeneration cycle, and low efficiency of regenerated activated carbon prepared by existing waste activated carbon regeneration methods, and to provide a method for the resource utilization of waste activated carbon from wax decolorization. The resource utilization method for waste activated carbon from wax decolorization described in this invention can achieve efficient resource utilization of waste activated carbon, reduce activated carbon production costs, and simultaneously improve or guarantee the performance indicators of regenerated activated carbon.

[0006] To achieve the above objectives, the present invention provides a method for the resource utilization of waste activated carbon from refined wax decolorization, the method comprising the following steps: (1) The waste activated carbon and anthracite are mixed, and then the resulting mixture is ball-milled to obtain mixed coal powder; (2) The mixed coal powder, coal tar and water are kneaded together, and then the resulting mixture is extruded and solidified to obtain shaped charcoal strips; (3) Carbonize the shaped carbon strip under air-isolated conditions; (4) Activate the carbonized material with high-temperature steam; The waste activated carbon contains charcoal, diatomaceous earth, and paraffin wax. Based on the total weight of the waste activated carbon, the charcoal content is 50-60% by weight, the diatomaceous earth content is 20-30% by weight, and the paraffin wax content is 10-20% by weight.

[0007] Preferably, in step (1), the mass ratio of the waste activated carbon to the anthracite is 3-10:100.

[0008] Preferably, the ash content of the anthracite is ≤3%.

[0009] Preferably, in step (1), the ball milling process results in the proportion of particles smaller than 200 mesh in the obtained material being >90%.

[0010] Preferably, in step (2), the mass ratio of the mixed coal powder, the coal tar and the water is 100:(32-38):(10-15).

[0011] Preferably, in step (2), the kneading conditions include: a temperature of 60-70°C and a time of 8-12 minutes.

[0012] Preferably, in step (2), the molding pressure of the extrusion molding is 14-18 MPa.

[0013] Preferably, in step (3), the carbonization conditions include: a heating rate of 8-15℃ / min, a carbonization temperature of 600-650℃, and a time of 20-40min.

[0014] Preferably, in step (3), the carbonization process results in the volatile matter content of the carbonized charcoal strip being 8-12%.

[0015] Preferably, in step (3), the carbonization process results in the carbonized charcoal strip having a strength ≥98%.

[0016] Preferably, in step (4), the activation conditions include: a temperature of 880-920°C and a time of 150-200 min.

[0017] Preferably, in step (4), the temperature of the high-temperature steam is 210-230°C.

[0018] According to the technical solution of this invention, based on the conventional production process of anthracite-based activated carbon, the porous structure and skeletal characteristics of lignin and diatomaceous earth in the waste activated carbon from wax decolorization are utilized as pore-forming agents and reinforcing agents during the mixing process. On the one hand, they promote pore development during the carbonization and activation stages, and on the other hand, they can significantly improve the mechanical strength and wear resistance of activated carbon. This allows it to work synergistically with anthracite to improve the adsorption capacity and mechanical strength of the final activated carbon, making it more suitable for dynamic adsorption environments. At the same time, it reduces the use of anthracite raw materials and lowers production costs. Attached Figure Description

[0019] Figure 1This is a process flow diagram of the method for resource utilization of waste activated carbon after decolorization by refined wax, as described in this invention. Detailed Implementation

[0020] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0021] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] like Figure 1 As shown, the method for resource utilization of waste activated carbon from refined wax decolorization according to the present invention includes the following steps: (1) The waste activated carbon and anthracite are mixed, and then the resulting mixture is ball-milled to obtain mixed coal powder; (2) The mixed coal powder, coal tar and water are kneaded together, and then the resulting mixture is extruded and solidified to obtain shaped charcoal strips; (3) Carbonize the shaped carbon strip under air-isolated conditions; (4) Activate the carbonized material with high-temperature steam; The waste activated carbon is generated during the decolorization process of refined wax. The waste activated carbon contains charcoal, diatomaceous earth, and paraffin wax. Based on the total weight of the waste activated carbon, the content of charcoal is 50-60% by weight, the content of diatomaceous earth is 20-30% by weight, and the content of paraffin wax is 10-20% by weight.

[0023] In a preferred embodiment, based on the total weight of the spent activated carbon, the content of charcoal is 55-58% by weight, the content of diatomaceous earth is 24-30% by weight, and the content of paraffin is 15-18% by weight. The charcoal has a mesh size of 200, a methylene blue content of 180 mg / g, and an iodine value of 1000 mg / g. The diatomaceous earth has a mesh size of 100 and a specific surface area of ​​45 cm². 2 / g. The paraffin wax is the solid paraffin wax remaining after decolorization of refined wax, with a melting point of 58-62℃.

[0024] In step (1), the mass ratio of the waste activated carbon to the anthracite can be 3-10:100, preferably 4-8:100, and more preferably 5-7:100.

[0025] In the method described in this invention, the ash content of the anthracite is ≤3%, preferably 2.1-3%. In a specific embodiment, the anthracite can be Taixi anthracite.

[0026] In step (1), the ball milling process results in a material having a particle size of less than 200 mesh with a particle size greater than 90%. Preferably, the ball milling process results in a material having a particle size of less than 200 mesh with a particle size of 95-99%. The ball milling process is carried out in a ball mill or a roller mill.

[0027] In step (2), the mass ratio of the mixed coal powder, the coal tar, and the water can be 100:(32-38):(10-15), preferably 100:(33-37):(11-14). The coal tar is medium-temperature coal tar with a density of 1.15-1.21 g / cm³ and a moisture content of ≤3%, purchased from Ningxia Hongxize Energy Co., Ltd.

[0028] In step (2), the kneading conditions may include a temperature of 60-70°C and a time of 8-12 minutes. Preferably, the kneading conditions include a temperature of 62-68°C and a time of 9-11 minutes. The kneading process can be carried out in a twin-shaft mixing tank or a kneader.

[0029] In step (2), the extrusion molding pressure can be 14-18 MPa, preferably 15-17 MPa. The extrusion molding process can be carried out in a hydraulic molding machine. The curing process includes: placing the extruded carbon strip at 10-40°C to dry it, so that the moisture content of the obtained shaped carbon strip is 1-3%.

[0030] In step (3), the carbonization conditions may include: a heating rate of 8-15℃ / min, a temperature of 600-650℃, and a time of 20-40min. Preferably, the carbonization conditions include: a heating rate of 9-12℃ / min, a temperature of 620-640℃, and a time of 25-35min. The carbonization process can be carried out in a carbonization furnace. The carbonization process removes volatiles from the charcoal strips, forms a preliminary porous structure, and hardens the charcoal strips, increasing their strength.

[0031] In step (3), the carbonization process results in the carbonized charcoal strip having a volatile matter content of 8-12% and a strength of ≥98%. Preferably, the carbonization process results in the carbonized charcoal strip having a volatile matter content of 9-11% and a strength of 98.5-99.9%.

[0032] In step (4), the activation conditions may include a temperature of 880-920℃ and a time of 150-200 min. Preferably, the activation conditions include a temperature of 890-910℃ and a time of 160-180 min. The activation process can be carried out in an activation furnace. The activation process can further develop pores, improve specific surface area, and enhance adsorption performance.

[0033] In step (4), the temperature of the high-temperature steam can be 180-240℃, preferably 210-230℃. The flow rate of the high-temperature steam can be 2-5L / min, preferably 3-4L / min.

[0034] The following examples further illustrate the method for resource utilization of waste activated carbon from wax decolorization according to the present invention. These examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures; however, the scope of protection of the present invention is not limited to the following examples.

[0035] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following embodiments are commercially available.

[0036] In the following examples and comparative examples, the relevant parameters of the intermediate products for preparing regenerated activated carbon from waste activated carbon were tested according to the following methods: Ash content test: The test shall be conducted in accordance with GB / T 7702.15-2008.

[0037] Moisture content test: The test shall be conducted in accordance with GB / T 7702.1-1997.

[0038] Volatile matter test: The test shall be conducted in accordance with GB / T 7702.16-1997.

[0039] Abrasion resistance test: The test shall be conducted in accordance with GB / T 7702.3-2008.

[0040] Methylene blue adsorption value: Tested according to GB / T 7702.6-2008.

[0041] Carbon tetrachloride adsorption rate: Tested according to GB / T 7702.13-1997.

[0042] Iodine adsorption value: Tested according to GB / T 7702.7-2008.

[0043] Specific surface area: The BET method (adsorption under nitrogen atmosphere, tested by Micromeritics ASAP2460 instrument) was used.

[0044] Activation yield: Activation yield = mass of activated carbon / mass of carbonized material × 100%.

[0045] Example 1 The waste activated carbon A1 used in this embodiment is waste activated carbon generated during the decolorization process of refined wax. The waste activated carbon A1 contains 55% by weight of wood charcoal (200 mesh, methylene blue 180 mg / g, iodine value 1000 mg / g, the same below), 25% by weight of diatomaceous earth (100 mesh, specific surface area 45 cm² / g, the same below) and 20% by weight of paraffin wax (melting point 60℃, the same below).

[0046] (1) The waste activated carbon A1 and anthracite B1 (purchased from Ningxia Taixi Coal Washing Plant, ash content 3%, the same below) are mixed at a mass ratio of 3:100. The resulting mixture is then fed to a ball mill for ball milling until the proportion of particles smaller than 200 mesh is 95%, thus obtaining mixed coal powder.

[0047] (2) The mixed coal powder, coal tar (purchased from Ningxia Hongxize Energy Co., Ltd., medium-temperature coal tar, density 1.18 g / cm³, the same below) and water obtained in step (1) are transported to a kneader at a mass ratio of 100:35:12 and kneaded at 60℃ for 10 min. Then the mixture is transported to a hydraulic molding machine and extruded under a molding pressure of 15 MPa. The molded strip is then placed at 25℃ and dried for 48 h for curing. The moisture content of the molded strip is 2.1%, and the molded carbon strip is obtained.

[0048] (3) Place the shaped carbon strips obtained in step (2) in a carbonization furnace and heat them to 630℃ for 30 minutes in an air-isolated state. The heating rate is 10℃ / min. The volatile matter content of the carbonized material is 9% and the wear resistance is 99%.

[0049] (4) Place the carbonized material in an activation furnace and introduce high-temperature steam at 220°C to activate it at 880°C for 150 min. The steam flow rate is 3 L / min to obtain regenerated activated carbon C1.

[0050] Example 2 The waste activated carbon A2 used in this embodiment is waste activated carbon generated during the decolorization process of refined wax. The waste activated carbon A2 contains 50% by weight of wood charcoal, 30% by weight of diatomaceous earth and 20% by weight of paraffin wax.

[0051] (1) Waste activated carbon A2 and anthracite B1 are mixed at a mass ratio of 3:100. The resulting mixture is then fed into a ball mill for ball milling until the proportion of particles smaller than 200 mesh is 96%, thus obtaining mixed coal powder.

[0052] (2) The mixed coal powder, coal tar and water obtained in step (1) are transported to a kneader at a mass ratio of 100:32:10 and kneaded at 60°C for 10 minutes. Then the mixture is transported to a hydraulic molding machine and extruded under a molding pressure of 14MPa. The molded strip is then placed at 25°C and dried for 48 hours for curing. The moisture content of the molded strip is 2.3%, and the molded carbon strip is obtained.

[0053] (3) Place the shaped carbon strips obtained in step (2) in a carbonization furnace and heat them to 640℃ for 30 minutes in an air-isolated state. The heating rate is 10℃ / min. The volatile matter content of the carbonized material was tested to be 11%, and the strength was 99%.

[0054] (4) Place the carbonized material in an activation furnace and introduce high-temperature steam at 220°C to activate it at 880°C for 150 min. The steam flow rate is 3 L / min to obtain regenerated activated carbon C2.

[0055] Example 3 The waste activated carbon A3 used in this embodiment is waste activated carbon generated during the decolorization process of refined wax. The waste activated carbon A3 contains 60% by weight of wood charcoal, 20% by weight of diatomaceous earth and 20% by weight of paraffin wax.

[0056] (1) Waste activated carbon A3 and anthracite B1 are mixed at a mass ratio of 5:100. The resulting mixture is then fed into a ball mill for ball milling until the proportion of particles smaller than 200 mesh is 93%, thus obtaining mixed coal powder.

[0057] (2) The mixed coal powder, coal tar and water obtained in step (1) are transported to a kneader at a mass ratio of 100:35:12 and kneaded at 60°C for 10 minutes. Then the mixture is transported to a hydraulic molding machine and extruded under a molding pressure of 16MPa. The molded strip is then placed at 25°C and dried for 48 hours to cure. The moisture content of the molded strip is 1.9%, and the molded carbon strip is obtained.

[0058] (3) Place the shaped carbon strips obtained in step (2) in a carbonization furnace and heat them to 650℃ for 30 minutes in an air-isolated state. The heating rate is 9℃ / min. The volatile matter content of the carbonized material was tested to be 10%, and the strength was 98.9%.

[0059] (4) Place the carbonized material in an activation furnace and introduce high-temperature steam at 220°C to activate it at 900°C for 180 min. The steam flow rate is 3 L / min to obtain regenerated activated carbon C3.

[0060] Example 4 The waste activated carbon A4 used in this embodiment is waste activated carbon generated during the decolorization process of refined wax. The waste activated carbon A4 contains 55% by weight of wood charcoal, 25% by weight of diatomaceous earth and 20% by weight of paraffin wax.

[0061] (1) Waste activated carbon A4 and anthracite B1 are mixed at a mass ratio of 3:100. The resulting mixture is then fed into a ball mill for ball milling until the proportion of particles smaller than 200 mesh is 92%, thus obtaining mixed coal powder.

[0062] (2) The mixed coal powder, coal tar and water obtained in step (1) are transported to a kneader at a mass ratio of 100:38:15 and kneaded at 70°C for 12 minutes. Then the mixture is transported to a hydraulic molding machine and extruded under a molding pressure of 18MPa. The molded strip is then placed at 25°C and dried for 48 hours to cure. The moisture content of the molded strip is 1.7%, and the molded carbon strip is obtained.

[0063] (3) Place the shaped carbon strips obtained in step (2) in a carbonization furnace and heat them to 650℃ for 30 minutes in an air-isolated state. The heating rate is 10℃ / min. The volatile matter content of the carbonized material is 8% and the strength is 99%.

[0064] (4) Place the carbonized material in an activation furnace and introduce high-temperature steam at 230°C. Activate at 920°C for 200 min. The steam flow rate is 3 L / min. Regenerated activated carbon C4 is obtained.

[0065] Example 5 Waste activated carbon was recycled to prepare regenerated activated carbon according to the method of Example 1, except that waste activated carbon A1 was replaced with waste activated carbon A2 (with the same composition as in Example 2), resulting in regenerated activated carbon C5.

[0066] Example 6 Waste activated carbon was recycled to prepare regenerated activated carbon according to the method in Example 1, except that the mass ratio of waste activated carbon A1 to anthracite B1 was adjusted to 2:100 to obtain regenerated activated carbon C6.

[0067] Example 7 Waste activated carbon was recycled to prepare regenerated activated carbon according to the method in Example 1, except that the mass ratio of waste activated carbon A1 to anthracite B1 was adjusted to 15:100 to obtain regenerated activated carbon C7.

[0068] Example 8 Waste activated carbon was recycled and regenerated activated carbon was prepared according to the method in Example 1. The difference was that the ball milling conditions were adjusted so that the proportion of particles smaller than 200 mesh was 85%, resulting in regenerated activated carbon C8.

[0069] Example 9 Waste activated carbon was recycled and regenerated activated carbon was prepared according to the method in Example 1, except that anthracite B1 was replaced with anthracite B2 (purchased from Yangquan, Shanxi, with an ash content of 5.2%), resulting in regenerated activated carbon C9.

[0070] Example 10 Waste activated carbon was recycled and regenerated activated carbon was prepared according to the method in Example 1. The difference was that the mass ratio of mixed coal powder, coal tar and water was adjusted to 100:40:12 to obtain regenerated activated carbon C10.

[0071] Example 11 Waste activated carbon was recycled and regenerated activated carbon was prepared according to the method in Example 1. The difference was that the mass ratio of mixed coal powder, coal tar and water was adjusted to 100:35:20 to obtain regenerated activated carbon C11.

[0072] Comparative Example 1 Waste activated carbon was recycled to prepare regenerated activated carbon according to the method in Example 1, except that the waste activated carbon A1 was replaced with an equal mass of anthracite B1 (i.e., no waste activated carbon was added), resulting in regenerated activated carbon D1.

[0073] Comparative Example 2 Regenerated activated carbon was prepared by resource utilization of waste activated carbon according to the method of Example 1, except that waste activated carbon A1 was replaced with waste activated carbon E1. Based on the total weight of waste activated carbon E1, its composition was: 80% by weight of wood charcoal, 10% by weight of diatomaceous earth, and 10% by weight of paraffin, resulting in regenerated activated carbon D2.

[0074] Comparative Example 3 Regenerated activated carbon was prepared by resource utilization of waste activated carbon according to the method of Example 1, except that waste activated carbon A1 was replaced with waste activated carbon E2. Based on the total weight of waste activated carbon E2, its composition was: 45% by weight of wood charcoal, 15% by weight of diatomaceous earth, and 40% by weight of paraffin, resulting in regenerated activated carbon D3.

[0075] Comparative Example 4 Regenerated activated carbon was prepared by resource utilization of waste activated carbon according to the method of Example 1, except that waste activated carbon A1 was replaced with waste activated carbon E3. Based on the total weight of waste activated carbon E3, its composition was: 30% by weight of wood charcoal, 55% by weight of diatomaceous earth, and 15% by weight of paraffin, resulting in regenerated activated carbon D4.

[0076] The performance parameters of the regenerated activated carbon prepared in the above embodiments and comparative examples are shown in Table 1 below.

[0077] Table 1

[0078] As can be seen from the results in Table 1, incorporating waste activated carbon as an additive into the production process of anthracite-based activated carbon according to the method described in this invention achieves efficient resource utilization of waste activated carbon, reduces the production cost of activated carbon, and improves or guarantees the performance indicators of regenerated activated carbon.

[0079] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for the resource utilization of waste activated carbon from refined wax decolorization, characterized in that, The method includes the following steps: (1) The waste activated carbon and anthracite are mixed, and then the resulting mixture is ball-milled to obtain mixed coal powder; (2) The mixed coal powder, coal tar and water are kneaded together, and then the resulting mixture is extruded and solidified to obtain shaped charcoal strips; (3) Carbonize the shaped carbon strip under air-isolated conditions; (4) Activate the carbonized material with high-temperature steam; The waste activated carbon contains charcoal, diatomaceous earth, and paraffin wax. Based on the total weight of the waste activated carbon, the charcoal content is 50-60% by weight, the diatomaceous earth content is 20-30% by weight, and the paraffin wax content is 10-20% by weight.

2. The method according to claim 1, characterized in that, In step (1), the mass ratio of the waste activated carbon to the anthracite is 3-10:100; Preferably, the ash content of the anthracite is ≤3%.

3. The method according to claim 1 or 2, characterized in that, In step (1), the ball milling process results in the proportion of particles smaller than 200 mesh in the obtained material being >90%.

4. The method according to claim 1, characterized in that, In step (2), the mass ratio of the mixed coal powder, the coal tar and the water is 100:(32-38):(10-15).

5. The method according to claim 1 or 4, characterized in that, In step (2), the kneading conditions include: a temperature of 60-70℃ and a time of 8-12 minutes.

6. The method according to claim 1, 4, or 5, characterized in that, In step (2), the molding pressure of the extrusion molding is 14-18 MPa.

7. The method according to claim 1, characterized in that, In step (3), the carbonization conditions include: a heating rate of 8-15℃ / min, a carbonization temperature of 600-650℃, and a time of 20-40min.

8. The method according to claim 1 or 7, characterized in that, In step (3), the carbonization process results in the volatile matter content of the carbonized charcoal strips being 8-12%; and / or, The carbonization process results in the carbonized carbon strip having an abrasion resistance of ≥98%.

9. The method according to claim 1, 7 or 8, characterized in that, In step (4), the activation conditions include: a temperature of 880-920℃ and a time of 150-200min.

10. The method according to any one of claims 1 and 7-9, characterized in that, In step (4), the temperature of the high-temperature steam is 210-230℃.